Performance evaluation of unmanned aerial vehicle communication by increasing antennas of cellular base stations - Rajesh Kapoor; Aasheesh Shukla; Vishal Goyal (Institute of Advanced Engineering and Science, 2022)
The utilization of unmanned aerial vehicles (UAVs) increases with increased performance of their communication link with the ground remote station. Integrating UAVs with existing cellular networks provides the possibility of enhanced performance of communication links. The base stations of existing cellular networks are installed with fixed number of antennas. The performance of UAV communication links can be further enhanced by increasing antennas of cellular base stations of existing networks using multiple antenna techniques such as multi ple input multiple output (MIMO). In this proposed scheme, Massive MIMO technology is used for UAV communications, wherein hundreds of antennas are mounted on cellular base stations. This set up provides significant advantage in terms of enhancement in per formance of UAV communication links, as compared to existing methods of UAV communication. In this paper, performance evaluation of UAV communication links is carried out by increasing the number of antennas at base stations of existing cellular networks. For this evaluation, firstly basic multiple antennas techniques such as point - to - point MIMO and multi - user MIMO (MU - MIMO) are covered based on existing studies and findings. Subsequently, an antenna dependent closed form expression for uplink channel capac ity of massive MIMO based UAV communication links is derived, with few numerical results.